Three-point bending test method and device for evaluating stress corrosion cracking of sulfur-resistant material of high hydrophobic gas field
By adopting three-point bending test methods and devices in high sulfur gas fields, the problems of inaccurate loading stress control and stress relaxation are solved, and high-accurate stress corrosion testing is achieved, which is suitable for large-scale tests in laboratories and on-site.
Patent Information
- Application Number
- CN202411669220.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
AI Technical Summary
In the evaluation of stress corrosion cracking of sulfur-resistant materials in high sulfur gas fields, the loading stress cannot be accurately controlled, the data is discrete and poor parallelism, and there is stress relaxation during the crack expansion process, which affects the development of the crack and even terminates the crack propagation, causing incomplete fracture of the specimen.
The three-point bending test method and device are adopted, including fixtures, samples and high-temperature autoclaves. The samples are loaded through the MTS test machine, combined with finite element analysis and scanning electron microscopy technology to accurately control the loading stress and observe crack propagation.
Accurate control of loading stress, improve the accuracy and repeatability of test data, overcome the problem of stress relaxation, can conduct large-scale tests in the laboratory or on-site, reduce experimental errors, and obtain more useful information about material stress corrosion.
Smart Images

Figure CN119643313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material stress corrosion cracking resistance evaluation, and in particular to a three-point bending test method and device for evaluating stress corrosion cracking of sulfur-resistant materials in high-sulphur-content gas fields. Background Art
[0002] Hydrogen embrittlement and hydrogen sulfide stress corrosion cracking (SCC) are one of the important forms of damage that cause many accidents in oil and gas fields and petrochemical equipment. Accidents that occur are often sudden and catastrophic, with no obvious signs before they occur, and are relatively difficult to prevent in advance. Hydrogen embrittlement and hydrogen sulfide stress corrosion cracking are brittle failures, and their formal characteristics are the generation of cracks, and the depth of the cracks is several orders of magnitude greater than the width. High-sulfur natural gas contains a large amount of hydrogen sulfide gas. The presence of hydrogen sulfide can cause metals to undergo hydrogen embrittlement, sulfide stress corrosion and other cracking phenomena. Preventing cracking is the core of material selection for high-sulfur gas fields.
[0003] Stress corrosion cracking (SCC) crack propagation generally goes through three stages: incubation period, crack propagation period and unstable fracture period. The incubation period can be long or short, sometimes up to several years. Once the stress corrosion cracking (SCC) crack nucleates, it enters the crack propagation period. The crack propagation rate during the crack propagation period can reach 10-6~10-3mm / min, which can be up to 106 times the uniform corrosion rate. After expanding to a certain extent, it enters the unstable fracture period and will break in a very short time. Stress corrosion cracking (SCC) cracks in the incubation period are difficult to detect. Although the crack propagation period can be detected, the time is short. Once the unstable fracture period is entered, it will lead to catastrophic accidents without warning. Therefore, how to realize stress corrosion cracking (SCC) crack detection during the incubation period is a difficult problem for scientific and technological workers.
[0004] Stress corrosion cracking (SCC) is the most complex form of corrosion, involving factors such as materials, mechanics, and electrochemistry. The funds used to study stress corrosion cracking (SCC) account for more than 70% of the world's corrosion research funds. The reason why stress corrosion cracking (SCC) research is so important is that the losses caused by stress corrosion cracking (SCC) are very large, often leading to sudden disasters. Secondly, the research on stress corrosion cracking (SCC) is not perfect enough. Since stress corrosion cracking (SCC) is the result of the combined effects of materials, stress, and environment, the mechanism of stress corrosion cracking (SCC) will also change with environmental changes. After decades of research, the academic community has generally agreed that it is impossible to find a unified mechanism to explain all the phenomena of stress corrosion cracking (SCC), but one system corresponds to one mechanism. This has caused uncertainty in stress corrosion cracking (SCC). The use of new materials or the application of old materials in new environments are risky, and their safety must be verified experimentally.
[0005] At present, the commonly used stress corrosion methods mainly include constant strain method, constant load method, slow strain rate tensile (SSRT) and fracture mechanics method. By testing with notched or prefabricated crack specimens, the relationship between stress level and crack growth rate can be obtained, and the KISCC value (stress corrosion cracking critical strength factor) can also be found, which is valuable for avoiding sudden stress corrosion accidents in design. However, during the crack expansion process, stress relaxation occurs, which affects the development of the crack and even terminates the crack expansion, resulting in incomplete fracture of the specimen. At the same time, in the process of real material evaluation, it usually contains defects such as microcracks, and the crack tip has stress concentration. How to effectively observe the rupture of the specimen with prefabricated cracks, and simulate the stress corrosion cracking of the actual component crack tip due to plastic deformation caused by stress concentration, is a difficulty that needs to be solved in the selection of materials for high-sulfur gas fields. For the selection of metal materials for high-sulfur gas fields, the stress corrosion test method needs to have several advantages: ① There are no special requirements for the corrosive environment medium. Researchers can design the medium conditions according to the actual working conditions or research needs, and can obtain experimental results in a short time, which greatly shortens the experimental cycle, and the experimental results have good reproducibility and repeatability; ② Overcome the shortcomings of the constant deformation test method that the stress relaxation caused by the constant deformation test method after the crack is initiated, so that the crack propagation stops, and the constant load test method causes the cross-sectional area to decrease after the crack is initiated, and the stress rises and the crack propagation becomes more and more serious; ③ This method can effectively simulate the service conditions of the material, which can not only reflect the essential factors of stress corrosion, but also obtain more useful information about the stress corrosion of the material, including fracture morphology, metallographic section, stress corrosion mechanism, microcrack morphology, maximum service load, etc.
[0006] The applicant found that for general smooth specimens, the crack incubation period will account for 90% of the entire fracture time, which is a long time. Only by proposing and studying new testing and evaluation methods for fracture toughness in corrosive media can we more accurately judge the critical stress and corresponding critical stress intensity factor of the material in the corrosive environment, so that the fracture toughness test value can better reflect the mechanical property value of the material itself. In addition, there are various methods for evaluating the stress corrosion performance of metals, and each method has its own special advantages in some cases. In a given case, whether the stress corrosion process occurs depends on the exposure conditions and the properties of the material. Before making a stress corrosion test plan, it is necessary to decide which type of test is appropriate, and such a decision mainly depends on the purpose of the test and the information required. The relevant provisions stipulate the preparation and application of various stress corrosion samples. Low-power microscopes are often used for sample inspection in result evaluation. However, when the cracks are not very obvious or covered and obscured by corrosion products, low-power microscopes cannot observe cracks, resulting in erroneous conclusions. Therefore, it is necessary to conduct metallographic examination and scanning electron microscopy on the cross section of the sample suspected of cracking to determine whether there are cracks, which also helps to determine whether the damage is caused by stress corrosion cracking or other forms of corrosion. Therefore, according to the three-point bending specimens recommended by ISO, ASTM, GB / T and other standards for obtaining the fracture toughness of metal materials, the matching fixtures are independently designed and processed, and can be loaded on the MTS testing machine, effectively overcoming the problem of loading difficulties caused by excessive loading loads. The wire cutting technology can be used to prefabricate the initial cracks of the loaded specimens, and the finite element analysis technology can be used to accurately obtain the stress distribution at the tip of the prefabricated cracks of the three-point bending specimens of metal materials. Combined with the fracture toughness calculation model of the prefabricated cracks of the three-point bending specimens of metal materials, the environmental critical fracture toughness KISCC of the metal materials can be effectively obtained. At the same time, combined with the scanning electron microscope (SEM) technology, the cracks caused by corrosion at the bottom of the pits and the pits can be effectively observed, and the crack initiation and expansion morphology can be more clearly understood; combined with the energy spectrum quantitative analysis (EDS) technology, the corrosion products at the crack initiation are analyzed, which is conducive to the study of the stress corrosion mechanism. The present invention has simple equipment, compact specimens, and convenient operation. Moreover, it has several major advantages required by the stress corrosion test method when selecting metal materials in high-sulfur gas fields. In view of the simplicity and economy of this method, it is suitable for long-term batch experiments in laboratories or on-site, and has good guiding significance for the selection of materials for actual high-sulfur gas fields. Summary of the invention
[0007] The purpose of the present invention is to provide a three-point bending test method and device for stress corrosion cracking evaluation of sulfur-resistant materials in high-sulfur gas fields, so as to solve the problems that the loading stress in the stress corrosion cracking evaluation of sulfur-resistant materials in high-sulfur gas fields cannot be accurately controlled, the data is discrete, and the parallelism is poor; during the crack expansion process, stress relaxation occurs, which affects the development of the crack and even stops the crack expansion, resulting in incomplete fracture of the specimen. In view of the above problems, the technical solution proposed by the present invention is:
[0008] A method for a three-point bending test device applied to stress corrosion cracking evaluation of sulfur-resistant materials in high-saturation gas fields, comprising:
[0009] The device for the three-point bending test applied to the stress corrosion cracking evaluation of sulfur-resistant materials in high-gas-content gas fields comprises a fixture, a sample, and a high-temperature autoclave. The fixture comprises a main body, the surface of the main body has a pair of fixing holes and a fixing cavity, the bottom surface of the main body is also provided with a base, and the fixing hole is fixed to the base by bolts, a loading hole is provided on one side of the fixing cavity, a pair of pads are installed on the other side of the fixing cavity, the pads are cylindrical, and the sample is placed on the pads, the fixture also comprises a loading fixing nut threadedly engaged with the loading hole, a loading rod sliding at one end of the fixing nut, and a loading pressure head sliding at the other end of the fixing nut , one end of the loading rod sliding in the fixed nut is connected to the loading pressure head, and the loading pressure head is insulated from the sample, the loading rod is connected to the MTS testing machine, and the MTS testing machine rotates the loading rod to drive the loading pressure head to make the sample produce a certain amount of deflection, the sample is located in the fixed cavity, a prefabricated crack is provided at the center of the sample, and is squeezed by the loading pressure head, the high-temperature and high-pressure autoclave includes a kettle body, an insulating bracket is installed inside the kettle body, a gas phase medium is provided in the upper half of the kettle body, and a liquid phase medium is provided in the lower half of the kettle body, and the fixture with the sample fixed is placed on the insulating bracket;
[0010] The method of three-point bending test for evaluating stress corrosion cracking of sulfur-resistant materials in high-saturated gas fields includes the following steps:
[0011] Step 1: According to the specific requirements of stress corrosion cracking evaluation of sulfur-resistant materials in high-sulfur gas fields, the dimensions of the fixture, the sample, and the base are designed, and the sample is assembled on the fixture;
[0012] Step 2: According to the loading level set in the experimental plan, considering the stress concentration at the tip of the notch, the deflection required for the loading stress, that is, the moving distance of the loading rod, is obtained through finite element modeling and calculation, and the parameters required for the MTS testing machine loading are determined, including the loading displacement speed and displacement of the MTS testing machine;
[0013] Step 3: Input the parameters into the MTS testing machine. When the load of the sample reaches the preset load, the MTS testing machine maintains the load, that is, the displacement of the upper clamping end of the MTS testing machine remains unchanged, and the loading fixing nut is tightened steadily and slowly. The fixture can be loaded on the MTS testing machine, effectively overcoming the problem of loading difficulty caused by excessive loading load;
[0014] Step 4: The MTS testing machine is unloaded, and the fixture with the sample that reaches the predetermined load is placed on the insulating bracket in the kettle body, and gas phase and liquid phase experiments are carried out in sequence. The kettle body has a 70MPa, 300°C dynamic circulating multiphase flow, and three groups of liquid phase and gas phase parallel experiments of the sample are carried out in the kettle body at the same time;
[0015] Step 5: Add the deoxygenated corrosive medium into the kettle, set the pressure and temperature experimental conditions in the kettle, and record the start time of the experiment. The experimental period is 720 hours, during which the temperature and pressure of the kettle are monitored and recorded;
[0016] Step 6: After the experiment is over, the kettle is opened after cooling and reducing pressure, and the fixture and the corrosive medium on which the sample having reached a predetermined load is fixed are taken out, and the physical property change and pH value of the corrosive medium are tested. At the same time, the sample is removed from the fixture, and then the fixture is photographed; the corrosion products at the cracks of the sample are collected, and then energy spectrum quantitative analysis (EDS) is performed on them;
[0017] Step 7: cold cutting is performed on the characteristic part (prefabricated crack loading position) of the sample (200), and the cutting size is 20 mm*10 mm. Subsequently, the sample (200) after cutting is ultrasonically cleaned with acetone, and then cleaned with alcohol. After air drying, it is polished with metallographic sandpaper (the sample is polished step by step with 400#, 600#, and 800# metallographic sandpaper respectively), and then it is cleaned and dried with distilled water and anhydrous ethanol, and a scanning electron microscope (SEM) analysis is performed to observe the surface cracks;
[0018] Step 8: Determine whether microcracks formed by stress corrosion are found on the left, bottom and right sides of the prefabricated cracks. If no microcracks are found in the sample, the environmental critical fracture toughness KISCC value of the sample is obtained according to the fracture toughness calculation model; if microcracks are found in the sample, reduce the loading level of step 2, and repeat steps 2 to 8 until no microcracks are found in the sample. Compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. The three-point bending test method and device for stress corrosion cracking evaluation of sulfur-resistant materials in high-gas-content gas fields. The fixture can be loaded on the MTS testing machine, effectively overcoming the problem of loading difficulties caused by excessive loading loads, and accurately loading stress to improve the accuracy of test data;
[0020] Second, the three-point bending test method and device for evaluating stress corrosion cracking of sulfur-resistant materials in high-gas-content gas fields. The shape and size of the test device of the present invention are suitable, and large-scale tests can be carried out in the laboratory or on-site to reduce experimental errors;
[0021] 3. The three-point bending test method and device for stress corrosion cracking evaluation of sulfur-resistant materials in high-porosity gas fields. The present invention introduces scanning electron microscopy (SEM) and energy spectrum quantitative analysis (EDS) technology to analyze the corrosion products at the cracks and observe the crack propagation. It can not only reflect the essential factors of stress corrosion, but also obtain more information about the fracture morphology, metallographic section, mechanism, microcrack morphology, maximum service load, etc. of stress corrosion of materials;
[0022] 4. The three-point bending test method and device for stress corrosion cracking evaluation of sulfur-resistant materials in high-gas-content gas fields can determine whether microcracks formed by stress corrosion are found on the left, bottom and right sides of the prefabricated cracks, and according to the fracture toughness calculation model, the environmental critical fracture toughness KISCC value for stress corrosion cracking evaluation of sulfur-resistant materials can be given. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of the three-point bending specimen fixture and accessories;
[0024] Figure 2 This is the assembly drawing of the three-point bending specimen fixture and accessories;
[0025] Figure 3 This is the placement diagram of the three-point bending specimen fixture in the high-temperature and high-pressure reactor after loading;
[0026] Figure 4 It is the loading curve diagram of three-point bending specimen;
[0027] Figure 5 This is the scanning electron microscope (SEM) image of the three-point bending sample taken out of the high temperature and high pressure reactor;
[0028] Figure 6 It is the size ratio and sampling direction diagram of the three-point bending specimen;
[0029] Figure 7 This is the dimension drawing of the three-point bending specimen fixture;
[0030] Figure 8 It is the loading curve diagram of three-point bending specimen;
[0031] Fig. 9 This is the SEM microscopic morphology of sample 1;
[0032] Fig.10 This is the SEM microscopic morphology of sample 2;
[0033] Fig.11 This is the SEM microscopic morphology of sample 3.
[0034] In the figure: 100, fixture; 1001, main body; 1002, fixing hole; 1003, loading hole; 1004, loading rod; 1005, cushion block; 1006, loading fixing nut; 1007, loading pressure head; 200, sample; 300, high temperature and high pressure autoclave; 3001, autoclave body; 3002, insulating bracket; 3003, liquid medium; 3004, gas medium. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] See also Figure 1 - Fig.11The present invention provides a technical solution: a device for a three-point bending test for stress corrosion cracking evaluation of sulfur-resistant materials in high-gas-content gas fields, comprising a fixture 100, a sample 200, and a high-temperature autoclave 300. The fixture 100 comprises a main body 1001, the surface of the main body 1001 has a pair of fixing holes 1002 and a fixing cavity, the bottom surface of the main body 1001 is also provided with a base, and the fixing hole 1002 is fixed by bolts and the base, a loading hole 1003 is provided on one side of the fixing cavity, a pair of pads 1005 are installed on the other side of the fixing cavity 1003, the pads 1005 are cylindrical, the sample 200 is placed on the pads 200, the fixture 100 also comprises a loading fixing nut 1006 threadedly engaged with the loading hole 1003, a loading rod 1004 sliding on one end of the fixing nut 1006, and a loading rod 1004 sliding on the other end of the fixing nut 1006. The loading head 1007 is movable, and one end of the loading rod 1004 sliding in the fixed nut 1006 is connected to the loading head 1007, and the loading head 1007 is insulated from the sample 200. The loading rod 1004 is connected to the MTS testing machine. The MTS testing machine rotates the loading rod 1004 to drive the loading head 1007 to make the sample 200 have a certain degree of deflection. The sample 200 is located in the fixed cavity, and a prefabricated crack is provided at the center of the sample 200, and is squeezed by the loading head 1007. The high-temperature and high-pressure autoclave 300 includes a autoclave body 3001, and an insulating bracket 3002 is installed inside the autoclave body 3001. The upper half of the autoclave body 3001 is provided with a gas phase medium 3004, and the lower half of the autoclave body 3001 is provided with a liquid phase medium 3003. The fixture 100 fixed with the sample 200 is placed on the insulating bracket 3002.
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] See also Figure 1 - Fig.11 The present invention provides a technical solution: a method for a three-point bending test device for evaluating stress corrosion cracking of sulfur-resistant materials in high-saturated gas fields, comprising the following steps:
[0039] Step 1: According to the specific requirements of stress corrosion cracking evaluation of sulfur-resistant materials in high-sulfur gas fields, the dimensions of the fixture 100, the sample 200, and the base are designed, and the sample 200 is assembled on the fixture 100;
[0040] Step 2: According to the loading level set in the experimental plan, considering the stress concentration at the notch tip, the deflection required for the loading stress, i.e., the moving distance of the loading rod 1004, is obtained through finite element modeling calculation, and the parameters required for the MTS testing machine loading are determined, including the loading displacement speed and displacement of the MTS testing machine;
[0041] Step 3: Input the parameters to the MTS testing machine. When the load of the sample 200 reaches the preset load, the MTS testing machine maintains the load, that is, the displacement of the upper clamping end of the MTS testing machine remains unchanged, and the loading fixing nut 1006 is tightened steadily and slowly. The fixture 100 can be loaded on the MTS testing machine, effectively overcoming the problem of loading difficulty caused by excessive loading load.
[0042] Step 4: The MTS testing machine is unloaded, and the fixture 100 with the sample 200 that reaches the predetermined load is placed on the insulating bracket 3002 in the kettle body 3001, and gas phase and liquid phase experiments are carried out in sequence. The kettle body 3001 has a 70MPa, 300°C dynamic circulating multiphase flow, and three groups of liquid phase and gas phase parallel experiments are carried out in the kettle body 3001;
[0043] Step 5: Add the deoxygenated corrosive medium into the kettle 3001, set the pressure and temperature experimental conditions in the kettle 3001, and record the start time of the experiment. The experimental period is 720 hours, during which the temperature and pressure of the kettle 3001 are monitored and recorded;
[0044] Step 6: After the experiment is over, after cooling and reducing the pressure, the kettle 3001 is opened, the fixture 100 and the corrosive medium fixed with the sample 200 reaching the predetermined load are taken out, and the physical property change and pH value of the corrosive medium are tested. At the same time, the sample 200 is removed from the fixture 100, and then the fixture 100 is photographed; the corrosion products at the cracks of the sample 200 are collected, and then the energy spectrum quantitative analysis (EDS) is performed on them;
[0045] Step 7: cold cutting is performed on the characteristic part of the sample 200 (prefabricated crack loading position), and the cutting size is 20mm*10mm. Then the cut sample 200 is ultrasonically cleaned with acetone, and then cleaned with alcohol. After air drying, it is polished with metallographic sandpaper (400#, 600#, and 800# metallographic sandpaper are used to polish the sample step by step), and then it is cleaned and dried with distilled water and anhydrous ethanol, and a scanning electron microscope (SEM) analysis is performed to observe its surface cracks;
[0046] Step 8: Determine whether microcracks formed by stress corrosion are found on the left, bottom and right sides of the prefabricated crack. If no microcracks are found in sample 200, obtain the environmental critical fracture toughness KISCC value of sample 200 according to the fracture toughness calculation model; if microcracks are found in sample 200, reduce the loading level of step 2, and repeat steps 2 to 8 until no microcracks are found in sample 200.
[0047] In order to further prove the feasibility of the present invention, an experimental example is given below to illustrate.
[0048] Experimental example
[0049] 1. Process specimens, fixtures, joints, screws and other accessories according to the design dimensions
[0050] The mechanical properties of the casing steel material are shown in the table below. The three-point bending specimen is a metal material processing specimen recommended by ISO, ASTM, GB / T and other standards. The standard three-point bending specimen used in this test is shown in the attached figure of the specification. Figure 6 The sample size ratio complies with the national standard GB4161-2007, S / W ≥ 5, 1.0 = W / B = 4.0 and 0.45 = a / W = 0.7. The size of the three-point bending sample fixture is shown in the attached figure of the specification. Figure 7 shown.
[0051] Three standard 115mm×15mm×5mm longitudinal arc notch specimens were taken from the casing body area. All test specimens were cut in the TL direction (where T is circumferential direction and L is longitudinal direction) at mid-thickness.
[0052]
[0053] 2. Installation of the specimen
[0054] The fixture 100 includes a main body 1001, the surface of the main body 1001 has a pair of fixing holes 1002 and a fixing cavity, the bottom surface of the main body 1001 is also provided with a base, and the fixing hole 1002 is fixed by bolts and the base, a loading hole 1003 is provided on one side of the fixing cavity, and a pair of pads 1005 are installed on the other side of the fixing cavity 1003, the pads 1005 are cylindrical, and the sample 200 is placed on the pads 200, the fixture 100 also includes a loading fixing nut 1006 threadedly engaged with the loading hole 1003, a loading rod 1004 sliding on one end of the fixing nut 1006, and a loading pressure head 1007 sliding on the other end of the fixing nut 1006, the end of the loading rod 1004 sliding in the fixing nut 1006 is connected to the loading pressure head 1007, and the loading pressure head 1007 is insulated from the sample 200.
[0055] 3. Sample loading
[0056] The fixture 100 is loaded by the MTS testing machine, and the corresponding parameters are input to start the loading experiment. When the load of the sample 200 reaches the predetermined load, the tensile testing machine maintains the load, that is, the displacement of the upper clamping end remains unchanged, and the loading fixing nut 1006 is tightened steadily and slowly, effectively overcoming the problem of loading difficulty caused by excessive loading load.
[0057] The loading loads and curves of the three samples 200 are shown in the following table and the attached figure of the specification. Figure 8 .
[0058]
[0059] 4. Three-point bending stress corrosion test under simulated working conditions
[0060] After the high-temperature and high-pressure three-point bending stress corrosion specimen is loaded, the fixture 100 and the specimen 200 are gently removed as a whole, placed in a high-temperature and high-pressure autoclave 300, and the deoxygenated corrosive medium (organic salt mud) is added. The high-temperature and high-pressure autoclave cover 300 is closed. After the pressure test is qualified, the high-temperature and high-pressure three-point bending stress corrosion experiment can be carried out after sufficient deoxygenation operation. The temperature is first raised to the specified temperature (150°C) and the high-temperature and high-pressure autoclave 300 is pressurized according to the partial pressure of each corrosive gas (total pressure 30MPa) before the experiment is started. The experimental period is 30 days, during which the temperature and pressure of the high-temperature and high-pressure autoclave are monitored and recorded.
[0061] 5. Sample processing
[0062] After the experiment, the physical property changes and pH value of the corrosive medium were tested, and the fixture 100 and the sample 200 were immediately taken out and photographed. After the sample 200 was unloaded and taken out, the corrosion products at the cracks were collected for energy spectrum quantitative analysis (EDS), and then the characteristic parts (pre-crack loading positions) were immediately cold cut, and the cutting size was 20mm*10mm. Then, the sample (200) was polished step by step with 400#, 600#, and 800# water sandpaper, respectively, and washed and dried with distilled water and anhydrous ethanol, and a scanning electron microscope (SEM) analysis was performed to observe the surface cracks of the sample 200. The SEM microscopic morphology is shown in the attached figure of the specification. Figures 9 to 11 As shown in the figure, no microcracks formed by stress corrosion were found when the left, bottom and right sides of the notch were enlarged, but pitting pits existed on the surface of the specimen.
[0063] 6. KISCC value calculation
[0064] According to the fracture toughness calculation model given in GB4161-2007 "Metallic Material Plane Strain Fracture Toughness KIC Test Method", the corresponding relationship between the stress intensity factor K determined in the metal pipe fracture toughness detection method and the actual crack length a is as follows:
[0065]
[0066] L is the span, in mm; W is the specimen width, in mm; B is the specimen thickness, in mm; F is the load at the force application point, in KN; a is the actual length of the crack, in mm.
[0067] It can be concluded that the environmental critical fracture toughness KISCC of the casing steel in a high sulfur corrosive gas medium environment with a pressure of 30 MPa and a temperature of 150°C is 131.19 MPa·m1 / 2.
Claims
1. A method for a three-point bending test device for evaluating stress corrosion cracking of sulfur-resistant materials in high-saturated gas fields, characterized in that: include: The device for a three-point bending test for stress corrosion cracking evaluation of sulfur-resistant materials in high-gas-content gas fields comprises a fixture (100), a sample (200), and a high-temperature autoclave (300). The fixture (100) comprises a main body (1001). The surface of the main body (1001) has a pair of fixing holes (1002) and a fixing cavity. One side of the fixing cavity is provided with a loading hole (1003). The other side of the fixing cavity (1003) is provided with a pair of pads (1005). The fixture (100) also comprises a loading fixing nut (1006) threadedly engaged with the loading hole (1003), and a fixing nut (1006) slidingly engaged with the loading hole (1003). The high temperature and high pressure autoclave (300) comprises a loading rod (1004) and a loading pressure head (1007) sliding on the other end of the fixing nut (1006); the sample (200) is located in the fixing cavity and is squeezed by the loading pressure head (1007); the high temperature and high pressure autoclave (300) comprises a autoclave body (3001); an insulating support (3002) is installed inside the autoclave body (3001); a gas phase medium (3004) is provided in the upper half of the autoclave body (3001); a liquid phase medium (3003) is provided in the lower half of the autoclave body (3001); and the fixture (100) fixed with the sample (200) is placed on the insulating support (3002); The method of three-point bending test for evaluating stress corrosion cracking of sulfur-resistant materials in high-saturated gas fields includes the following steps: Step 1: designing the dimensions of the fixture (100) and the sample (200) according to the specific requirements of stress corrosion cracking evaluation of sulfur-resistant materials in high-sulfur gas fields, and assembling the sample (200) on the fixture (100); Step 2: According to the loading level set in the experimental plan, the moving distance of the loading rod (1004) required for the loading stress is obtained by finite element modeling calculation, and the displacement speed and displacement amount of the MTS testing machine loading are determined; Step 3: Inputting parameters into the MTS testing machine, when the load of the sample (200) reaches a predetermined load, the MTS testing machine maintains the load; Step 4: The MTS testing machine is unloaded, and the fixture (100) fixed with the sample (200) reaching a predetermined load is placed on the insulating bracket (3002) in the kettle body (3001), and gas phase and liquid phase experiments are performed in sequence; Step 5: Add the deoxygenated corrosive medium into the kettle (3001), set the pressure and temperature experimental conditions in the kettle (3001), and record the start time of the experiment. The experimental period is 720 hours, during which the temperature and pressure of the kettle (3001) are monitored and recorded; Step 6: After the experiment is finished, after cooling and reducing the pressure, the kettle (3001) is opened, the fixture (100) on which the sample (200) having reached a predetermined load is fixed and the corrosive medium are taken out, and the physical property changes and pH value of the corrosive medium are tested. At the same time, the sample (200) is removed from the fixture (100), and then the fixture (100) is photographed; the corrosion products at the cracks of the sample (200) are collected, and then energy spectrum quantitative analysis (EDS) is performed on them; Step 7: cold cutting is performed on the characteristic part (prefabricated crack loading position) of the sample (200), and the cutting size is 20 mm*10 mm. The sample (200) after cutting is then ultrasonically cleaned with acetone, and then cleaned with alcohol, air-dried and polished, and then cleaned and dried with distilled water and anhydrous ethanol, and subjected to scanning electron microscopy (SEM) analysis to observe surface cracks. Step eight: determining whether microcracks formed by stress corrosion are found on the left side, bottom and right side of the prefabricated crack; if no microcracks are found in the sample (200), obtaining the environmental critical fracture toughness KISCC value of the sample (200) according to the fracture toughness calculation model; if microcracks are found in the sample (200), reducing the loading level of step two, repeating steps two to eight until no microcracks are found in the sample (200).